Severe Haemolytic Anaemia, a Rare Presentation of Nutritional Vitamin B12 Deficiency: A Case Report - Siddiqui, Aamir (Nepalese Medical Journal, 2019)
Vitamin B12 deficiency usually presents with megaloblastic anemia, pancytopenia, and neurological symptoms. The cause is usually, nutritional deficiency, increase demand, decrease absorption. This report describes a case with symptoms of apathy and findings suggestive of severe hemolytic anemia, diagnosed with vitamin B12 deficiency. Haemolysis is a rare hematological finding in cases of B12 deficiency, and descriptions of a nutritional vitamin B12 deficiency, without evidence of pernicious anaemia, causing haemolysis, are even scarcer, and this paper was intended to draw physicians’ attention to this rare form of presentation.